Serum cytokines in ulcerative colitis of various clinical activity - Ye. A. Konovich; I. L. Halif; M. V. Shapina; K. E. Shirokikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine frequency of detection and level of circulating cytokines at ulcerative colitis (UC) and assess their interrelation with clinical activity and efficacy of conservative treatment. Material and methods. The serum level of IL-2, IL-4, IL-6, IL-8, IL-10, granulocyte-macrophage colonystimulating factor (GM-CSF), IFN-γ and TNF-α was studied in 37 ulcerative colitis patients. Investigation was carried out by «Bio-Plex» protein analyzer («Bio-Rad», USA). Moderately severe and severe forms of UC were diagnosed in 15 and 18 patients respectively, mild — in 4, resistance and sensitivity for conservative treatment were detected in 15 and 22 patients. Surgical treatment was carried out in 14 patients. The control group included 20 blood donors. Results. In patients with moderately severe, severe forms and in the control group IL-6 and IL-10 were revealed in 33,3, 61,1 (р<0,05), 5% of cases and 26,6, 50 (р<0,05), 10% of cases respectively. Substantial increase of IL-6 and IL-10 level was observed in severe form of UC (42,4±21,2 and 22,7±6,4 a pg/ml) as compared to the control group (1,5±1,8 and 5,2±4,1). In groups of patients, resistant and sensitive to conservative treatment, frequency of circulating IL-6 detection was 86,6 and 22,7% (р<0,05), level of IL-6 — 53,4±24,5 and 2,0±0,62 (р<0,05); detection rate of IL-10 — 66,6 and 9% (р<0,05), level of IL-10-31,6±7,4 and 7,1±6,9 (р<0,05) respectively. Three and more circulating cytokines were revealed in 80% of patients, resistant to conservative treatment and in 22,7% (р<0,05) of patients responded to treatment. The profile of IL-6, IL-8 and IL-10 was observed in 60 and 4,5% (р<0,05) patients of these groups respectively. Conclusions. Frequency of detection and level of circulating cytokines IL-6 and IL-10 is considerably higher at severe forms of UC and in patients, resistant to conservative treatment. Expansion of circulating cytokines spectrum, mainly IL-6, IL-8 and IL-10 profile in combination to 1–3 of the other studied cytokines (GM-CSF, IFN-γ, TNF-α) is typical for resistant form of disease.